A double challenge: Managing precocious puberty in congenital adrenal hyperplasia with gonadotropin releasing hormone agonist - Hossain, Md. Ashraful; Tofail, Tania; Banu, Hurjahan; Sultana, Nusrat; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Congenital adrenal hyperplasia is the most common cause of peripheral precocious puberty in boys. Treatment with hydrocortisone usually halts the progression of peripheral precocity. However, being on this treatment, a few cases may be complicated by central precocious puberty. In such cases, treatment with a Gonadotropin-Releasing Hormone agonist (GnRHa) usually prevents further pubertal development and the acceleration of bone age. Here, we present a case of an 8-year-old boy who was diagnosed with peripheral precocious puberty due to congenital adrenal hyperplasia. He had a history of the appearance of pubic hair and phallic enlargement at 6 years of age, aggressive behavior, and hyperpigmentation. Notably, he had bilateral testicular microlithiasis and a varicocele. Despite treatment with hydrocortisone and fludrocortisone, his pubertal progression and advancement of bone age continued. Clinical and hormonal evaluation subsequently confirmed conversion to central precocious puberty. Addition of a GnRHa to his glucocorticoid and mineralocorticoid regimen successfully arrested further pubertal progression. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S48]